Comparative Study of Immunohistochemical, Hematoxylin & Eosin Staining and its Diagnostic Importance in Hirschsprungas Disease (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: H and E stain; hirschsprung's disease; immunehistochemi-cal stain; hirschsprung’s disease; H and E stain.